FORMATION OF THE LOCAL BUDGET DEVELOPMENT BUDGETS DURING MARTIAL LAW AND POST-WAR RECOVERY - ROZHKO, Oleksandr; DEMYDENKO, Liudmyla; NAKONECHNA, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Financing the post-war recovery of the territorial communities requires significant resources. Local budgets suffered the most from the hostilities, as they lost a significant part of their revenue sources. The priority is not development, but survival and recovery of the UTCs. Budgets for development, which should be directed to the socio-economic development of UTCs, have been significantly reduced due to lack of funds. The article analyses the main sources of filling the budgets for development of local budgets, which were used in the pre-war period after the start of the decentralisation process. The main changes in legislation on possible sources of filling the budgets for development of local budgets are studied. The main areas of expenditures that can be made at the expense of the budgets for development are identified. It is established that currently, according to the legislation, the main sources of filling budgets for development are funds from the use of municipal property, concession payments, capital transfers from other budgets and local borrowings. The State Fund for Regional Development (SFRD) was also identified as one of the possible sources. An analysis of the pre-war functioning of the SFRD showed that by 2022, the effective operation of this mechanism had not been established. This is due to several reasons, including the lack of a well-established framework for selecting the most needed projects, delays in funding, and the absence of an effective methodology for evaluating projects submitted for the competition. This led to the suspension of the SFRD's work even before the outbreak of hostilities. It has been determined that the list of possible sources of funding for the development budget has been constantly changing since the adoption of the Budget Code. The most recent changes to the possible sources of budgets for development are dated February 2022. Given the outbreak of the war, this means that there is a real need to review the legal basis for filling these budgets. One of the possible ways to fill the budgets for development is through the State Fund for Regional Development in a new format in line with the government's plans to reform it. Another possible way is to amend the legislation to include external donor assistance and international borrowing as sources of budget for development revenues. This will reduce the time required to restore territorial communities in the post-war period.
Keywords: budget for development; local budgets; local budget revenues; regional development fund; amalgamated territorial communities